Development of Electrospun Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Monolayers Containing Eugenol and Their Application in Multilayer Antimicrobial Food Packaging - Figueroa-Lopez, Kelly J.; Cabedo, Luis; Lagaron, Jose M.; Torres-Giner, Sergio (Frontiers in Nutrition, 2020)
In this research, different contents of eugenol in the 2.5-25 wt.% range were first incorporated into ultrathin fibers of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) by electrospinning and then subjected to annealing to obtain antimicrobial monolayers. The most optimal concentration of eugenol in the PHBV monolayer was 15 wt.% since it showed high electrospinnability and thermal stability and also yielded the highest bacterial reduction against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). This eugenol-containing monolayer was then selected to be applied as an interlayer between a structural layer made of a cast-extruded poly(3-hydroxybutyrate) (PHB) sheet and a commercial PHBV film as the food contact layer. The whole system was, thereafter, annealed at 160 °C to develop a novel multilayer active packaging material. The resultant multilayer showed high hydrophobicity, strong adhesion and mechanical resistance, and improved barrier properties against water vapor and limonene vapors. The antimicrobial activity of the multilayer structure was also evaluated in both open and closed systems for up to 15 days, showing significant reductions (R ≥ 1 and < 3) for the two strains of food-borne bacteria. Higher inhibition values were particularly attained against S. aureus due to the higher activity of eugenol against the cell membrane of Gram positive (G+) bacteria. The multilayer also provided the highest antimicrobial activity for the closed system, which better resembles the actual packaging and it was related to the headspace accumulation of the volatile compounds. Hence, the here-developed multilayer fully based on polyhydroxyalkanoates (PHAs) shows a great deal of potential for antimicrobial packaging applications using biodegradable materials to increase both quality and safety of food products.